Scorpion Venom Analgesic Peptide, BmK AGAP Inhibits Stemness, and Epithelial-Mesenchymal Transition by Down-Regulating PTX3 in Breast Cancer - Kampo, Sylvanus; Ahmmed, Bulbul; Zhou, Tingting; Owusu, Lawrence; Anabah, Thomas Winsum; Doudou, Natacha Raissa; Kuugbee, Eugene Dogkotenge; Cui, Yong; Lu, Zhili; Yan, Qiu; Wen, Qing-Ping (Frontiers in Oncology, 2019)
A scorpion peptide reported to exhibit both analgesic and antitumor activity in animal models may present as an alternative therapeutic agent for breast cancer. We aimed to investigate the effect of Buthus martensii Karsch antitumor-analgesic peptide (BmK AGAP) on breast cancer cell stemness and epithelial-mesenchymal transition (EMT). We treated MCF-7 and MDA-MB-231 cells with different concentrations of rBmK AGAP and observed that rBmK AGAP inhibited cancer cell stemness, epithelial-mesenchymal transition (EMT), migration, and invasion. Analysis by qPCR, ELISA, western blot, immunofluorescence staining, sphere formation, colony assay, transwell migration, and invasion assays demonstrated rBmK AGAP treatment decreased the expressions of Oct4, Sox2, N-cadherin, Snail, and increased the expression of E-cadherin. rBmK AGAP inhibited breast cancer cell stemness, EMT, migration, and invasion by down-regulating PTX3 through NF-κB and Wnt/β-catenin signaling Pathway in vitro and in vivo. Xenograft tumor model confirmed inhibition of tumor growth, stem-like features, and EMT by rBmK AGAP. Thus, rBmK AGAP is a potential therapeutic agent against breast cancer and related pain. Key Words: Scorpion Venom Analgesic Peptide, rBmK AGAP, Stemness, Epithelial-Mesenchymal Transition, Pentraxin 3, Wnt/β-catenin signaling.